DSP control implementation particularities for an active DC traction substation experimental model - Suru, Constantin Vlad; Linca, Mihaita; Subtirelu, Eugen (2017 10th International Symposium on Advanced Topics in Electrical Engineering (ATEE), 2017)
The paper focuses on the design and implementation of the control algorithm for the experimental model of an active DC traction substation, paying particular attention to the design flaws and DSP implementation unforeseen problems. The design flaws combined with unforeseen behavior of the DSP control board can lead to system faults like short-circuits or overvoltage and can produce destructive malfunctions to the power equipment. Therefore, the DSP signals which can produce hazards and must be treated with maximum caution are the gating signals for the power IGBTs. These signals are usually generated using hysteresis current regulators and are available at the DSP digital output ports. While generating or inhibiting the gating signals is a matter of control algorithm and is the subject of design flaws (the control algorithm generates a logic "high" signal for the both transistors of an inverter leg, for example) the overlap of the gating signals for one or more inverter legs can appear also because of the initialization steps of the DSP control board. This is a hazardous behavior of the control board and should not normally appear, but caution must be taken especially in the initialization stages (program compiling and loading) when the output ports can change state for short periods of time. To avoid destructive faults, the IGBTs gating signals must be hardware inhibited until the system is fully initialized and ready to run. The behavior of the dSpace DS1103 control board was investigated for both design flaws and hardware unexpected actions. The implemented control algorithm is for a three phase active power filter which also must function as a current output voltage inverter.